Price of pandemic : weakened trade system exposed - Rogerson, Evan (2020)
The global trade outlook following the onslaught of the COVID-19 pandemic is undeniably dark. For a durable recovery it is imperative to build on the leadership that some governments have shown and revive the multilateral system.